Cereal Prices and Child Undernutrition in Ethiopia - Brenton, Paul (Taylor and Francis, 2022)
This paper looks at how changing cereal prices affect child undernutrition in Ethiopia. It derives height for age (stunting) and weight for height (wasting) as indicators of child undernutrition from the two most recent years of the Livings Standards Measurement Survey and utilizes market prices for key cereals, teff, wheat, and maize at the enumeration area across all regions of the country. Using a panel data fixed effects model, the analysis finds that, contrary to previous studies, rising cereal prices are positively associated with improved child stunting rates for children between ages 6 months and 5 years. There is no evidence to suggest that cereal prices have a significantly greater impact on height for age for children that come from households who are net sellers of these crops. Cereal prices do not appear to be associated with wasting, which is a shorter-term negative health outcome.